Effects of a 6 Week Yoga Intervention on Executive Functioning in Women Screening Positive for Adult ADHD: A Pilot Study - Fritz, Kathryn; O'Connor, Patrick J. (Frontiers in Sports and Active Living, 2022)
Purpose Little is known about the effects of yoga training in adults with ADHD symptoms. This pilot study sought to determine the feasibility and selected psychological effects of 6 weeks of yoga training in women screening positive for adult ADHD compared to a wait-list control group. Methods A randomized trial was conducted with 32 adult women (18–24 years) who volunteered after screening positive for adult ADHD as assessed by the Adult ADHD Self-Report Scale (ASRS). Participants were randomized to 6 weeks of Bikram yoga training or to a wait-list control group. The yoga intervention consisted of two 90-min classes per week. Multilevel models were used to test hypothesized interactions of yoga-induced improvements compared to controls across time (baseline, 3 weeks, and 6 weeks). The primary outcomes assessed inhibitory control, cognitive flexibility and working memory using the NIH Toolbox. Separate models with trait mindfulness, trait anxiety and expectations for change in either attention or working memory as covariates tested whether these variables mediated the changes in the three measures of executive function. Secondary outcomes included mood, perceived functional impairment and motivation for, and hyperactivity during, the cognitive tests. Results No adverse events were observed. Attendance averaged 91.7% among the 69% of the sample that did not dropout. No significant Group X Time interactions were found for any of the psychological outcomes and the null executive function findings were unchanged when including the covariates. Conclusion Six-weeks of yoga training twice per week is potentially feasible for women experiencing ADHD symptoms, but an exercise stimulus of this duration and magnitude yields no beneficial cognitive or mood outcomes.